State housing policy to ensure the well-being of the population - Kakhovka, O. B. (Ways to Improve Construction Efficiency, 2018)
The article formulates the principles of the state housing policy, which determine the directions of its sustainable development to ensure the well-being of the population. The importance of the government taking measures to improve the conditions and quality of living of the population due to the significant influence of the development of the housing construction industry on the dynamics of social and economic indicators of the country and individual regions. The main goals of the state housing policy are defined and generalized, and the tools and mechanisms of the state housing policy aimed at improving the current situation in providing the population with housing are proposed.